PARATHYROID HORMONE AND THE RISK OF INCIDENT HYPERTENSION: THE ATHEROSCLEROSIS RISK IN COMMUNITIES (ARIC) STUDY - Yao, Lu (J Hypertens, 2016)
BACKGROUND: Recent evidence suggests that parathyroid hormone (PTH) has effects on vascular smooth muscle cells, the renin-angiotensin system and kidney function, but less is known about its role in the development of hypertension. The distribution of serum PTH also varies by race. METHODS AND RESULTS: Therefore, we examined the relation between PTH and incident hypertension and tested for interaction by race among 7,504 ARIC participants (1,264 black, 6,240 white, median age 56 years) without initial hypertension in 1990–1992. During a median follow-up of 6 years, 1,487 white and 509 black participants developed hypertension. In the overall study population, PTH was not associated with incident hypertension after adjustment for demographics and behavioral risk factors [HR highest vs. lowest quintiles, 95%CI: 1.11 (0.96–1.28); P for linear trend 0.02]. Although the interaction was not statistically significant (P= 0.60), there was some evidence that the PTH-hypertension association differed by race. Among blacks, PTH was positively associated with incident hypertension, independent of demographics and behavioral risk factors (P for linear trend 0.003). Among whites, PTH was not associated with hypertension risk. Results were similar when comparing participants with elevated versus non-elevated PTH (≥65 vs. <65 pg/mL): HR in blacks: 1.24 (1.02–1.54); HR in whites: 0.95 (0.78–1.16). CONCLUSIONS: In this large community-based cohort, PTH levels, overall, were not independently associated with the risk of hypertension. However, we found some evidence that PTH may be associated with hypertension in blacks. Future research should continue to explore potential race differences in the PTH-hypertension association.